2010
DOI: 10.2527/jas.2009-2256
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic profiling of 2 muscles from 5 different pure pig breeds using surface-enhanced laser desorption/ionization time-of-flight proteomics technology1

Abstract: The objectives of this study were to evaluate the influence of different pure pig breeds and muscle types on the expression of muscle proteins, as well as their interactions, and second, to find biomarkers for breed and muscle types. A total of 126 male pigs, including 43 Landrace, 21 Duroc, 43 Large White, 13 Pietrain, and 6 Belgian Landrace, were slaughtered at the age of 174 +/- 6 d. Samples from the semimembranosus muscle (SM) and LM were collected 24 h postmortem. Proteomic spectra were generated on an an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Ultimately, the successful combination of transcriptomics, proteomics and metabolomics demonstrates the importance of an integrated systems biology approach to muscle deposition in the pig. A high throughput analysis, based on SELDI-TOF (Surface Enhanced Laser Desorption Ionization Time of Flight) that uses special chromatographiclike probe surfaces (ProteinChip arrays) has also been used to characterize and differentiate the proteome of longissimus dorsi and semimembranosus muscles in three high muscle deposition pig breeds (Landrace, Duroc, Large White, Pietrain and Belgian Landrace) [46]. The authors found two potential biomarkers for breed classification and 4 biomarkers of interest to differentiate the two muscles and suggest the need for further validation.…”
Section: Proteomics Of Muscle and Pork Productionmentioning
confidence: 99%
“…Ultimately, the successful combination of transcriptomics, proteomics and metabolomics demonstrates the importance of an integrated systems biology approach to muscle deposition in the pig. A high throughput analysis, based on SELDI-TOF (Surface Enhanced Laser Desorption Ionization Time of Flight) that uses special chromatographiclike probe surfaces (ProteinChip arrays) has also been used to characterize and differentiate the proteome of longissimus dorsi and semimembranosus muscles in three high muscle deposition pig breeds (Landrace, Duroc, Large White, Pietrain and Belgian Landrace) [46]. The authors found two potential biomarkers for breed classification and 4 biomarkers of interest to differentiate the two muscles and suggest the need for further validation.…”
Section: Proteomics Of Muscle and Pork Productionmentioning
confidence: 99%
“…Although these animals were genetically related we used them as comparisons for each other without further validation using different breeds. Previous studies with different breeds showed that breed and muscle type did not affect the number of peaks per spectrum in SELDI-TOF experiments, while a few of these peaks indicated muscle fibre type-specific proteins (Mach et al, 2010). Marcos et al (2013a, b), comparing four different pure breeds (Duroc, Large White, Landrace, and Pietrain) using the same technique, showed associations between protein peaks and meat quality traits, mainly water-holding capacity and texture.…”
Section: Biomarkers For Resources For High-quality Dry-cured Ham Prodmentioning
confidence: 99%
“…The laser intensity was 3,000 nJ. The SELDI protein array spectra were further normalised and analysed as explained by Mach et al (2010).…”
Section: Seldi-tof-ms Analysesmentioning
confidence: 99%
“…In a previous work, Mach et al (2010) detected potential protein markers from GM muscle that could be used to classify raw hams by breed type (Duroc, Large White, Landrace, and Piétrain). The animals from Mach et al (2010) were used in the present study to produce dry-cured hams with the objective to assess the differences between breeds on dry-cured ham quality. Besides, the work also aimed to investigate of the relationships between protein fingerprinting in GM muscle of raw hams and the final quality of dry-cured hams.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation